2022
DOI: 10.3389/fimmu.2022.874589
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Regulate PD-1/PD-L1 Immunosuppression

Abstract: Anti-programmed cell death 1 (PD-1) or anti-PD-ligand (L) 1 drugs, as classic immune checkpoint inhibitors, are considered promising treatment strategies for tumors. In clinical practice, some cancer patients experience drug resistance and disease progression in the process of anti-PD-1/PD-L1 immunotherapy. Tumor-associated macrophages (TAMs) play key roles in regulating PD-1/PD-L1 immunosuppression by inhibiting the recruitment and function of T cells through cytokines, superficial immune checkpoint ligands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 134 publications
(119 reference statements)
0
63
0
Order By: Relevance
“…Accumulating evidence has indicated that TAMs in TME is associated with the prognosis and immunological characteristics of a variety of cancers (Lam et al, 2019;Li et al, 2019;Xiao N et al, 2021). TAMs can mediate PD-1 drug resistance in HCC through the PD-L1 pathway and regulation of T cells (Pu and Ji, 2022). Molecular biomarkers of TAMs could be used for risk-stratification and response prediction of cancer treatments, though the fundamental cognition of cellular structures and molecular landscapes in liver cancer remains difficult to define.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that TAMs in TME is associated with the prognosis and immunological characteristics of a variety of cancers (Lam et al, 2019;Li et al, 2019;Xiao N et al, 2021). TAMs can mediate PD-1 drug resistance in HCC through the PD-L1 pathway and regulation of T cells (Pu and Ji, 2022). Molecular biomarkers of TAMs could be used for risk-stratification and response prediction of cancer treatments, though the fundamental cognition of cellular structures and molecular landscapes in liver cancer remains difficult to define.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed phenotype shifting of TAMs from immune-suppressive CD68 + CD163 + TAM2 to pro-inflammatory/anti-tumor CD68 + CD163 - TAM1. TAM2 has long been recognized to be associated with tumor progression, metastasis and poor prognosis, and recent evidence revealed TAM2 suppressed the effect of ICIs via secreting anti-inflammatory cytokines and exosomes, and also increasing superficial PD-L1 ( 39 ). So the phenotype transition driven by intra-arterial chemotherapy could also enhance the efficacy of anti-PD therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no statistical difference in the expression of TAM (M2) between the composite score subgroups, the in ltration by TAM (M2) was high and statistically signi cant in the high-risk IRGPI or m 6 A risk score subgroups, which is consistent with the results of our survival analysis. In addition, tumor drug resistance is the main cause of chemotherapy failure, and studies have shown that TAMs are closely related to the drug resistance of tumors [39,40]. Chimeric antigen receptor macrophages (CAR-M) have been demonstrated to enter solid tumors and survive in the tumor environment, triggering long-lasting adaptive immune responses [4,37].…”
Section: Discussionmentioning
confidence: 99%